2016
DOI: 10.1038/onc.2016.377
|View full text |Cite
|
Sign up to set email alerts
|

ZNF750 is a lineage-specific tumour suppressor in squamous cell carcinoma

Abstract: ZNF750 controls epithelial homeostasis by regulating epidermal-differentiation genes, a role underscored by its pathogenic mutations in esophageal squamous cell cancers (SCCs). However, the precise role of ZNF750 in SCC cell biology remains unclear. In this study, we report that ZNF750 is exclusively deleted, mutated and underexpressed in human SCCs, and low ZNF750 expression is associated with poor survival. Restoration of wildtype, but not mutant ZNF750 protein uniquely inhibited the malignant phenotypes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 21 publications
6
94
0
1
Order By: Relevance
“…Several reports have shown that the expression of ZNF750 is decreased in cancer tissues compared with normal tissues [5,6,10], and the mutation of ZNF750 inhibited the activation of differentiation genes and caused functional deterioration [9,14]. Some studies have shown that the decreased expression of ZNF750 promoted cell growth, migration, and invasion in squamous cell carcinoma [5,6,10], and Cohen et al [15] revealed that the downregulation of ZNF750 decreased apoptosis in human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have shown that the expression of ZNF750 is decreased in cancer tissues compared with normal tissues [5,6,10], and the mutation of ZNF750 inhibited the activation of differentiation genes and caused functional deterioration [9,14]. Some studies have shown that the decreased expression of ZNF750 promoted cell growth, migration, and invasion in squamous cell carcinoma [5,6,10], and Cohen et al [15] revealed that the downregulation of ZNF750 decreased apoptosis in human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ZNF750 was immunohistochemically assessed using the peroxidase-antiperoxidase complex method in accordance with the previously reported protocol [10]. Antihuman ZNF750 polyclonal antibody (1: 200; HPA023012; SigmaAldrich, St. Louis, MO, USA) was used as the primary antibody, and anti-mouse/rabbit antibody (EnVision/HRP, anti-mouse/rabbit, K5001; DAKO Japan, Tokyo, Japan) was used as the secondary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As several reports have shown, ZNF750 interacts with KLF4 to induce differentiation genes [14,25,26] . KLF4 is a member of the Krüppel-type zinc finger transcription factor family [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in silico analysis showed that ESCC individuals with ZNF750 mutations were more likely to present LN metastasis, and to have shorter disease-free survival compared with those without ZNF750 mutations. ZNF750 is a novel tumor suppressor identified by our lab and others (5,11,12), and it exhibits frequent loss-of-function mutations and genomic deletions across different types of squamous cell carcinomas in a lineage-specific fashion. In vitro experiments have shown that ZNF750 regulates the proliferation, differentiation, adhesion and migration of squamous cells, supporting its putative role in tumor metastasis.…”
mentioning
confidence: 99%